Transcriptomic profiling for prolonged drought in Dendrobium catenatum - Wan, Xiao (Sci Data, 2018)
Orchid epiphytes, a group containing at least 18,000 species, thrive in habitats that often undergo periodic drought stress. However, few global gene expression profiling datasets have been published for studies addressing the drought-resistant mechanism of this special population. In this study, an experiment involving the effect of continuous drought treatments on an epiphytic orchid, Dendrobium catenatum, was designed to generate 39 mature-leaf-tissue RNA-seq sequencing datasets with over two billion reads. These datasets were validated by a series of quality assessments including RNA sample quality, RNA-seq read quality, and global gene expression profiling. We believe that these comprehensive transcriptomic resources will allow a better understanding of the drought-resistant mechanisms of orchid epiphytes.